Analisis Kepuasan Pasien Rawat Jalan terhadap Pelayanan Farmasi di Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Zaleha Ulfa; Dessy Hermawan; Riyanti Riyanti; Koidar Amirus; Nurhalina Sari (Universitas Malahayati Lampung, 2022)
ABSTRACK The drug administration worldview has moved from drug direction to medication and patient direction. Fulfillment is a significant piece of wellbeing administrations since patient fulfillment can't be isolated from the nature of wellbeing administrations. This study aims to determine the relationship between outpatient satisfaction with pharmaceutical services at Pertamina Bintang Amin Hospital in Bandar Lampung. The independent factors are reliability, tangible, responsiveness, assurance, empathy and the dependent factor is patient satisfaction. It's a cross-sectional study that uses a quantitative approach. All patients/families of outpatients taking medication at the outpatient pharmacy unit within one week of working hours were included in this study. Samples were taken using a technique called purposive sampling. Multivariate and univariate data analysis was performed. known that there is a significant relationship between reliability, tangibles, responsiveness, assurance, and empathywith patient satisfaction with pharmaceutical services, obtained respectively – each value [(reliability; p-value = 0.037: OR = 2,130),(tangibles = p-value = 0.017 : OR = 2.251), (responsiveness ; p-value = 0.036: OR = 2.080), (assurance ; p-value = 0.001 : OR = 3.931) and (empathy ; p-value = 0.027 : OR = 2.141). Known the most dominant variable that affects outpatient satisfaction with pharmaceutical services is assurance with a p.value of 0.001: Exp B (OR): 5,262. Patients' satisfaction with pharmacy services is affected by the following factors: dependability, tangibles, responsiveness; assurance; and empathy; the most prominent of these is the assurance dimension. Keywords: Patient Satisfaction,Outpatient, Pharmaceutical Services ABSTRAK Pandangan dunia pemberian obat telah berpindah dari arah obat ke arah pengobatan dan pasien. pemenuhan adalah bagian penting dari pelayanan kesehatan karena pemenuhan pasien tidak dapat dipisahkan dari sifat pelayanan kesehatan. Penelitian ini bertujuan untuk mengetahui hubungan kepuasan pasien rawat jalan terhadap pelayanan farmasi di RS Pertamina Bintang Amin Bandar Lampung. Faktor independen adalah reliability, tangible, responsiveness, assurance,empaty dan faktor dependen kepuasan pasien.Merupakan penelitian potong lintang yang menggunakan pendekatan kuantitatif. Semua pasien/keluarga pasien rawat jalan yang minum obat di unit farmasi rawat jalan dalam waktu satu minggu jam kerja diikutsertakan dalam penelitian ini. Sampel diambil dengan menggunakan teknik yang disebut purposive sampling. Analisis data multivariat dan univariat dilakukan. Keandalan, bukti fisik, respon cepat, jaminan, dan empati dengan kepuasan pasien terhadap pelayanan kefarmasian terbukti memiliki hubungan yang signifikan. Setiap skor diperoleh [(reliability ; p-value = 0,037: OR = 2,130),(tangibles = p-value = 0,017 : OR = 2,251), (responsiveness ; p-value = 0,036: OR = 2,080), (assurance ; p-value = 0,001 : OR = 3,931) dan (empathy ; p-value = 0,027 : OR = 2,141).Diketahui variabel yang paling dominan yang mempengaruhi kepuasan pasien rawat jalan terhadap pelayanan farmasi adalah assurance dengan nilai p.value 0.001: Exp B (OR) : 5.262 Kepuasan pasien terhadap pelayanan kefarmasian dipengaruhi oleh faktor-faktor berikut: ketergantungan, bukti fisik, daya tanggap, jaminan, dan empati, yang paling menonjol adalah dimensi jaminan. Kata Kunci : Kepuasan Pasien, Rawat Jalan, Pelayanan Farmasi